A distributed knowledge base for manufacturing scheduling - Varela, M.L.R. (2005)
This paper describes a distributed knowledge base for manufacturing scheduling. A great variety of scheduling problems can occur in manufacturing. For solving different problems, usually different methods are required The distributed knowledge base enables sharing information about scheduling problems and corresponding solving methods in a widened search space. These methods can be remotely available and accessible through the Internet. Running several methods enables obtaining alternative results for a given problem, consequently, contributing for a better scheduling decision making. An important aspect is that end users and scheduling methods' providers alike can easily and continuously update this knowledge base.